Building theory of green supply chain management for the chemical industry: An emerging economy context. Issue 5 (17th March 2020) - Shohan, Shohanuzzaman; Ali, Syed Mithun; Kabir, Golam; Ahmed, S.K. Kafi; Haque, Tasmiah; Suhi, Saima Ahmed
Abstract : Purpose: In Bangladesh, the chemical industry is one of the expanding industries based on current statistical data analysis. Green supply chain management (GSCM) is pivotal in order to compete with the global competition. This paper main aim is to discuss a systematic approach to build a structural outline. The purpose of the proposed structural outline is to predict the constructive implementation of GSCM especially on chemical industry in Bangladesh. Design/methodology/approach: This proposed structural framework evaluates the suitable interrelationship next to the barriers of GSCM in the Bangladesh's chemical industry. Here, on the basis of literature review and survey from expert opinions by the use of the Delphi methodology in total eight barriers were concluded. Here additionally, MICMAC analyses were applied to determine the driving and dependence power. Furthermore, the frameworks outline for the barriers were included by means of total interpretive structural modeling (TISM) method. Findings: Based on the analysis, the most significant barriers were found lack of supporting laws and guidance from the government and cost of disposal of hazardous products. Research limitations/implications: The TISM technique only has implemented to develop the framework, whereas other tools or structural equation modeling (SEM) technique can be used to develop and validate the frameworks for barriers. Originality/value: In this research, Delphi method questionnaire generated based on the GSCM in the Bangladesh chemical sector. This study will assist the industrial managers to assess and evaluate the crucial sectors, whereas they should give priority to apply the GSCM in the Bangladesh chemical industry.